Auditory steady state response can predict declining EF in healthy elderly individuals - Xiaopeng Mao; Xiaopeng Mao; Nelly Shenton; Sadasivan Puthusserypady; Martin Johannes Lauritzen; Krisztina Benedek (Frontiers in Aging Neuroscience)
BackgroundThe aging population imposes significant economic and societal challenges, underscoring the need for early detection of individuals at risk of cognitive decline prior to the onset of clinical symptoms. This study explores the association between gamma-band Auditory Steady-State Responses (ASSRs) and subclinical cognitive decline using longitudinal data from healthy volunteers in the Metropolit Birth Cohort (MBC).MethodsLongitudinal recordings of cognitive test results and ASSRs at 40 Hz stimulation were analyzed. Generalized Linear Models (GLMs) were employed to determine the association between ASSR characteristics and cognitive performance with an emphasis on Executive Function (EF) at ages 61–68. Additionally, Vision Transformers (ViTs) were trained to distinguish between individuals with declining and stable cognitive performance.ResultsSubjects with declining cognitive performance through midlife showed a larger area of entrainment and delayed neural assembly of ASSRs compared to those with stable cognitive performance. These neurophysiological changes were correlated with poorer EF, as measured by the Stockings of Cambridge (SOC) task. The ViTs trained and cross-validated on time-frequency-transformed Electroencephalograms (EEGs) achieved an average cross-subject accuracy of 51.8% in identifying cognitive decline.ConclusionGamma-band ASSR characteristics are linked to early cognitive decline in middle-aged individuals, offering potential as biomarkers. However, the limited predictive accuracy of ML models emphasizes the need for further refinement to enhance their clinical applicability.